Assessment of nutritional status and food consumption of patients with depression (Research, Society and Development, 2022)
To assess whether there is an association between nutritional status and food consumption in patients with depression. The study was developed at the Psychosocial Care Center (CAPS), located in the city of Sobral - CE, with 100 patients with depressive disorder, aged between 20 and 59 years, both sexes. Socioeconomic, anthropometric and food consumption data were collected through a Food Frequency Questionnaire (FFQ). The project was approved by the Research Ethics Committee, under opinion No. 2,596,743. Of the 100 participants in the sample, 67% (n=67) were women, in the age group “under 39 years old”, 55% (n=55), black 51% (n=51), consensual union∕married 56% (n=56) and income of up to one minimum wage 55% (n=55). When analyzing the nutritional status, both sexes had a greater number of overweight and obese participants. The prevalence of overweight was 89%, being 58% female and 31% male. As for food consumption, there was no difference between the participants, according to the Body Mass Index (BMI) (p > 0.05). There is a high proportion of overweight among the patients evaluated and this was not associated with food consumption.